2001
DOI: 10.1112/s002461070000171x
|View full text |Cite
|
Sign up to set email alerts
|

Systems of Diagonal Equations Over p-Adic Fields

Abstract: Work partially supported through a fellowship from the David and Lucile Packard Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…suffices for these primes. One can compare this with the result given in [4] for systems of forms which all have the same degree (although this result is improved in [6]). Theorem 1 is a trivial consequence of the following theorem, which is unfortunately somewhat more complicated to state.…”
Section: Introductionmentioning
confidence: 74%
“…suffices for these primes. One can compare this with the result given in [4] for systems of forms which all have the same degree (although this result is improved in [6]). Theorem 1 is a trivial consequence of the following theorem, which is unfortunately somewhat more complicated to state.…”
Section: Introductionmentioning
confidence: 74%
“…In the special case K=double-struckQp, Knapp has shown that it suffices for s to satisfy s>32R2d2 if p>2 and s>4R2d2 if p=2 [5, Theorem 2], which is the best result to date for this case. The bounds for systems over a general K coming from Theorem A thus differ from the best bounds for systems over Qp only by a factor of 2.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much work in the recent literature concerning systems of diagonal equations and their relation to AC (see [6,7,11,12,13,14,15]). In particular, it is known that AC holds for pairs of diagonal forms of equal degree k, except possibly when k takes the form p τ (p − 1) or 3 · 2 τ (p = 2), and that AC holds also for pairs of diagonal forms of distinct odd degrees.…”
Section: Introductionmentioning
confidence: 99%